2019
DOI: 10.1177/1359105319873956
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and subjective well-being of Ghanaian parents of children with special needs: The mediating role of resilience

Abstract: The study explored the mediating role of resilience in the relationship between spirituality and subjective well-being of 107 Ghanaian biological parents raising children with special needs. Results from mediational analyses revealed that spirituality indirectly influenced life satisfaction, positive affect and negative affect through resilience. Specifically, greater levels of spirituality predicted greater resilience, which successively led to greater life satisfaction, greater positive affect and reduced ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 41 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…In the same light as the previous paragraph, Gerson [60] reported that spirituality predicted PSS, resilience, and life satisfaction and added that spirituality was a more robust predictor of resilience than PSS, which required positive emotions to mediate its contribution on resilience. Confirming that, Dey et al [61] advocated that a greater level of spirituality predicted greater resilience, which explains the further link to greater levels of life satisfaction and positive affect. Almost similarly, studies on resilience in nations with recent war history disclosed that spirituality predicted resilience through the decreased aggressive behaviour [62].…”
Section: Introductionmentioning
confidence: 91%
“…In the same light as the previous paragraph, Gerson [60] reported that spirituality predicted PSS, resilience, and life satisfaction and added that spirituality was a more robust predictor of resilience than PSS, which required positive emotions to mediate its contribution on resilience. Confirming that, Dey et al [61] advocated that a greater level of spirituality predicted greater resilience, which explains the further link to greater levels of life satisfaction and positive affect. Almost similarly, studies on resilience in nations with recent war history disclosed that spirituality predicted resilience through the decreased aggressive behaviour [62].…”
Section: Introductionmentioning
confidence: 91%
“…Reasons given for this stark disparity include the peculiar behavioural problems exhibited by children with Autism Spectrum disorder and symptom severity ( Dieleman et al., 2018 ; Rivard et al., 2014 ). Amid these struggles and emotional turmoil, some parents have emerged stronger by employing adaptive coping and protective resources like religiosity, spirituality, hope, optimism and social support ( Dey et al., 2019 ; Trute et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…To assess the mechanisms of well-being production requires observing change within people who differ in theoretically relevant ways and assessing how their lives turn out (Garssen and Visser, 2016). However, previous investigations of spirituality and well-being, including high-quality reviews and meta-analyses, have nearly exclusively relied on cross-sectional samples (Ano and Vasconcelles, 2005; Hackney and Sanders, 2003; Jan et al, 2020; Sawatzky et al, 2005; Smith et al, 2003; Visser et al, 2010; Yonker et al, 2012), and have sampled from small sub-populations such as older adults (Lawler-Row and Elliott, 2009), urban African American women (Holt et al, 2003), rural Kenyan men (Goodman et al, 2020), and Ghanaian parents of children with special needs (Dey et al, 2019). Such limitations have been evident over 20 years (see, e.g.…”
mentioning
confidence: 99%